Prevalence and Associated Risk Factors of Hypertension Among People Aged 50 years and more in Banepa Municipality, Nepal - Manandhar, Kedar; Koju, R; Sinha, NP; Humagain, S (Kathmandu University Medical Journal, 2013)
Background Hypertension is a cardiovascular disorder rapidly emerging as a major public health problem in developing countries and is the most widely recognized modifiable risk factor for cardiovascular diseases. Objective  The objective of this study was to find out the prevalence and associated risk factors with hypertension among people aged 50 years and more in Banepa Municipality, Kavre, Nepal. Methods It is a cross- sectional, population based study which was carried out in Banepa Municipality from May 15 to June 15, 2009. Among total 11 wards of Banepa municipally, wards number 1, 3, 5, 6, 7, and 10 were selected by using Simple Random Sampling Technique and 405 subjects of people aged 50 years and more were selected for study from the selected wards by using Cluster Sampling. The structured interview method was used for collection of data. Mercury sphygmomanometers with standard cuff were used to measure the indirect auscultatory arterial blood pressure. Two consecutive blood pressure readings were taken and average of them was calculated to determine single value of blood pressure. Results The prevalence of hypertension was 44.9 percent (47.75% in male and 42.73% in females). Among them, only 32.9 percent (60/182) were previously diagnosed as hypertension. The higher proportion of hypertensive cases were in age > 65 years (55.49%) than in the age group < 65 years (36.32%). The prevalence of hypertension was seen positively associated with non vegetarian eating habits, alcohol consumption, and > 25 Body max index. Taking green leafy vegetable at least once a week was negatively associated with the prevalence of the hypertension. Conclusion  These findings provide important information on the prevalence, associated factors of hypertension in Banepa Municipality. Effective public health measures and strategies are needed to improve prevention, diagnosis and access to treatment of these 50 years and above population. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 35-38 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8015